2010
DOI: 10.1074/jbc.m109.094573
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin H Is an Additional Convertase of Pro-granzyme B

Abstract: The serine protease granzyme B (GrB) is the most potent proapoptotic cytotoxin of the granule exocytosis pathway of cytotoxic lymphocytes. GrB is synthesized as a zymogen (proGrB) and activated in cytotoxic granules by the lysosomal cysteine protease cathepsin C (CatC) which removes the N-terminal dipeptide Gly-Glu. It has been shown recently that mice lacking CatC nonetheless express significant residual GrB activity, indicating the presence of additional proGrB convertases. Here, we describe an assay to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 26 publications
2
48
0
Order By: Relevance
“…Our data support the conclusions of Méthot et al (25,26) who reported that very high fractional inhibition of the CatC activity by chronic administration of a CatC inhibitor is required to prevent the activation of NSPs in vivo. CatH has been shown to serve as a backup for CatC-mediated granzyme B activation in cytotoxic lymphocytes (38). In human neutrophil precursor cell lines we did not observe any additional convertase activity when CatC is inhibited in keeping with the results of Pham et al (19).…”
Section: Discussionsupporting
confidence: 79%
“…Our data support the conclusions of Méthot et al (25,26) who reported that very high fractional inhibition of the CatC activity by chronic administration of a CatC inhibitor is required to prevent the activation of NSPs in vivo. CatH has been shown to serve as a backup for CatC-mediated granzyme B activation in cytotoxic lymphocytes (38). In human neutrophil precursor cell lines we did not observe any additional convertase activity when CatC is inhibited in keeping with the results of Pham et al (19).…”
Section: Discussionsupporting
confidence: 79%
“…(93). As noted above, the main cathepsin responsible for granzyme activation is cathepsin C but, at least for granzyme B, the alternative pro-granzyme convertase is cathepsin H. Furthermore, even cathepsin C and H null mice exhibit some residual granzyme B activity, suggesting another mechanism of activation (40).…”
Section: Regulation Of Cell Cytotoxicity By Cystatinsmentioning
confidence: 99%
“…These results suggested that there are other peptidases involved in granzyme activation and, for granzyme B, cathepsin H was found as an additional peptidase. However, cytotoxic lymphocytes from cathepsin C and H null mice still retain residual granzyme B activity, implying that further peptidases are involved in granzyme B activation (40). In addition to activation of granule-localized serine peptidases, cathepsins are also involved in perforin processing in cytotoxic cells.…”
Section: Cysteine Cathepsins and Legumain As Regulators Of The Immunementioning
confidence: 99%
See 2 more Smart Citations